2016
DOI: 10.1186/s12885-016-2459-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of annexin A2 and annexin A4 expression in patients with cervical cancer

Abstract: BackgroundThe annexins (ANXs) have diverse roles in tumor development and progression, however, their clinical significance in cervical cancer has not been elucidated. The present study was to investigate the clinical significance of annexin A2 (ANXA2) and annexin A4 (ANXA4) expression in cervical cancer.MethodsANXA2 and ANXA4 immunohistochemical staining were performed on a cervical cancer tissue microarray consisting of 46 normal cervical epithelium samples and 336 cervical cancer cases and compared the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
0
20
0
4
Order By: Relevance
“…Annexin A2 (ANXA2), belongs to annexin family, is a calcium‐dependent phospholipid‐binding protein. ANXA2 is overexpressed in numerous tumours, including glioma . Aberrantly, expression of ANXA2 plays important roles in tumour development by regulating cell proliferation, apoptosis, invasion and metastasis …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Annexin A2 (ANXA2), belongs to annexin family, is a calcium‐dependent phospholipid‐binding protein. ANXA2 is overexpressed in numerous tumours, including glioma . Aberrantly, expression of ANXA2 plays important roles in tumour development by regulating cell proliferation, apoptosis, invasion and metastasis …”
Section: Introductionmentioning
confidence: 99%
“…The S100 proteins are low molecular weight proteins (10)(11)(12) that belong to the EF-hand calcium-binding proteins family and are only expressed in vertebrates. 3,4 S100A11(known as calgizzarin or S100C) is a member of the S100 proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study built a 12-gene-based prediction model, which performed well for the recurrence prediction of early cervical cancer [10]. Another study, using the same expression profile data, revealed that Annexin A2 (ANXA2) and ANXA4 are also molecular indicators of the recurrence risk of cervical cancer [11]. Overexpression of ANXA2 and ANXA4 is associated with shorter disease-free survival [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another study, using the same expression profile data, revealed that Annexin A2 (ANXA2) and ANXA4 are also molecular indicators of the recurrence risk of cervical cancer [11]. Overexpression of ANXA2 and ANXA4 is associated with shorter disease-free survival [11]. However, additional molecular markers possibly exist and should be identified.…”
Section: Introductionmentioning
confidence: 99%